Synthesis and biological evaluation of 1, 3-dioxolane-based 5-HT1A receptor agonists for CNS disorders and neuropathic pain. (25th July 2018) - Franchini, Silvia; Bencheva, Leda Ivanova; Battisti, Umberto Maria; Tait, Annalisa; Sorbi, Claudia; Fossa, Paola; Cichero, Elena; Ronsisvalle, Simone; Aricò, Giuseppina; Denora, Nunzio; Iacobazzi, Rosa Maria; Cilia, Antonio; et al.
Aim: Targeting 5-HT1A receptor (5-HT1A R) as a strategy for CNS disorders and pain control.Methodology: A series of 1, 3-dioxolane-based 2-heteroaryl-phenoxyethylamines was synthesized by a convergent approach and evaluated at α1 -adrenoceptors and 5-HT1A R by binding and functional experiments. Absorption, distribution, metabolism, excretion and toxicity prediction studies were performed to explore the drug-likeness of the compounds.Results & conclusion: The most promising compound, the pyridin-4-yl derivative, emerged as a potent and selective 5-HT1A R agonist (pKi = 9.2; pD2 = 8.83; 5-HT1A /α1 = 135). In vitro it was able to permeate by passive diffusion MDCKII-MDR1 monolayer mimicking the blood–brain barrier and showed promising neuroprotective activity.